SUCCESSFUL REDUCTION OF INTRAOPERATIVE TRANSFUSIONS DURING CARDIAC SURGERY. Issue 12 (18th November 2016) - Tran, Minh-Ha; Milliken, Jeffrey; Merrill, Douglas
Abstract : Background: Intraoperative transfusion burden was identified as a practice improvement area within cardiac surgery. Objectives: Our project aimed to reduce intraoperative blood utilization during cardiac surgery. Methods: A multidisciplinary team analyzed cardiopulmonary bypass (CPB) surgery practice to identify risks for hemodilution. A suite of intraoperative blood conservation strategies, including retrograde autologous priming, was implemented. Data were analyzed comparing Pre to Post implementation time periods. Using descriptive statistics we analyzed intravenous fluid volume, intraoperative hematocrit (hct), and blood component units per case as outcome measures. Process control methodology was used to assess long term impact (sustainability) of our intervention. Results: Analysis of 136 (72 pre, 64 post) cases of elective of non-redo coronary artery bypass graft (CABG) surgery demonstrated reduction in hemodilution by a mean (±95% CI) of 973.7 mL (671.6–1275.9; p<0.001) resulting in improvement in on-pump hematocrit of over 2% between. The proportion of patients receiving any red cell transfusions during the off-pump phase of surgery improved from 47.2% to 26.6%. A similar analysis of 103 elective valve replacement (38 pre, 65 post implementation) cases found significant reductions in off-pump red cell, plasma, and platelet transfusions of 58% to 26%, 63% to 29%, and 71% to 39%, respectively. Finally, process control analysis of 388 cases spanning the intervention demonstrated sustained reductions in mean units/case transfused for red cells, plasma, and platelets. Conclusions: Through introduction and application of basic intraoperative blood conservation modalities, we successfully reduced intraoperative blood utilization during cardiac surgery. Improvements were significant and sustainable over time.Figure 1 Figure 2A Figure 2B Figure 2C